EFFECT OF INSULIN ON PROGESTERONE PROFILE AND CONCEPTION RATE IN CROSSBRED COWS - SHARMA, MRIDULA; GUPTA, H P; PRASAD, SHIV; AGARWAL, SANJAY (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on 48 crossbred cows aged 4-12 years, divided into four groups (n=12 in each group). In I, II and Ill (Treated) groups, insulin@ 0.25 IU/Kg (Human Mixtard®, Torrent Pharmaceuticals Ltd., India) was given subcutaneously daily for 4 days on days 0-3, 4-7 and 8-11 of estrous cycle, respectively and in control group PBS (s/c) was administered comparable to insulin suspension on 4-7 days of estrous cycle. Blood samples were collected on day 0, 5, 10, 16 and 21 and serum was separated for estimation of progesterone (P4). Serum P4 concentration on day 10 and 16 was significantly (P<0.05) higher in group I compared to other groups. Its concentration in all groups was significantly (P<0.05) lower on day O compared to day 16. It was also significantly (P<0.05) lower on day O and 5 compared to day 21 in I, II and Ill groups. P4 level in blood, on day 21 was significantly (P<0.01) higher in pregnant animals compared to non pregnant animals of all the groups. Conception rate in group I was higher, i.e. 58.33% followed by 41.66%, 25% and 16.67% in groups Ill, II and IV, respectively. Present study could be concluded that the treatment of cows with insulin on days 0-3 of estrous cycle had positive effect on improvement of conception rate.